Planejamento turístico responsável das praias Perequê e Castelhanos (Ilhabela-SP) - Seixas, Camila Lopes (Universidade Federal de São Carlos, 2020)
This research approaches responsible tourism planning on the beaches of Ilhabela (São Paulo, Brazil), which requires specific carefulness due to being an island. The discussion embraces issues related to time, work, spare-time, tourist profile and tourism segments and goes through different concepts from mass and mild tourism, responsible tourism, sustainable tourism, and tourism of experience. The systemic relations of local tourism and tourists are investigated aiming to introduce guidelines and an overview towards the responsible planning of the beaches of Ilhabela. This work takes the beaches Perequê and Castelhanos as study subjects, considering their opposed location that diverge because of the protection area declared by the “Plano de Manejo do Parque Estadual de Ilhabela” (Handling Plan for the State Park of Ilhabela) and the cultural, environmental, social and economic influences on each of them. Guidelines for a responsible planning of the beaches are presented as a result, both for entrepreneurships and tourists and the public power as well, involving management and promotion actions and public politics; all of it while taking into consideration the narrowing factors and the impact of public usage. It also features studies and analysis of the Perequê beach and Ilhabela’s tourism concerning the Pandemic and the Responsible Tourism seal adopted by the Tourism Ministry (Ministério do Turismo).
Responsible touristic planning of Perequê and Castelhanos beaches
Keywords: Gestão de praias; Turismo responsável; Turismo de sol e praia; Turismo de massa; Turismo de natureza; Beach management; Responsible Planning; Sun and beach; Mass tourism; Nature tourism; CIENCIAS SOCIAIS APLICADAS::TURISMO